2007
DOI: 10.1103/physrevb.76.085211
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic redshift of the optical gap in GdN

Abstract: We report measurements of the optical gap in a GdN film at temperatures from 300 to 6K, covering both the paramagnetic and ferromagnetic phases. The gap is 1.31eV in the paramagnetic phase and red-shifts to 0.9eV in the spin-split bands below the Curie temperature. The paramagnetic gap is larger than was suggested by very early experiments, and has permitted us to refine a (LSDA+U)-computed band structure. The band structure was computed in the full translation symmetry of the ferromagnetic ground state, assig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
152
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(183 citation statements)
references
References 30 publications
31
152
0
Order By: Relevance
“…However, optical absorption is dominated by direct transitions, whereas the minimum gap is expected to be between Γ and X in the band structure, as found previously for GdN. 17 We thus turn to an examination of the band structure calculated using QSGW , as shown in Figure 10. The calculation does indeed return a semiconducting and ferromagnetic ground state, with a direct gap at X of 0.94 eV and a minimum indirect gap between Γ and X of 0.31 eV.…”
Section: Comparison Of Spectroscopies With Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…However, optical absorption is dominated by direct transitions, whereas the minimum gap is expected to be between Γ and X in the band structure, as found previously for GdN. 17 We thus turn to an examination of the band structure calculated using QSGW , as shown in Figure 10. The calculation does indeed return a semiconducting and ferromagnetic ground state, with a direct gap at X of 0.94 eV and a minimum indirect gap between Γ and X of 0.31 eV.…”
Section: Comparison Of Spectroscopies With Theorymentioning
confidence: 99%
“…33 We have previously shown that for GdN the optical absorption edge in the paramagnetic state is reasonably well described by taking an average of the spin-down and spin-up direct band gaps. 17 Following this approach we obtain a spin averaged direct QSGW gap at X of 1.59 eV for EuN, somewhat higher than the FM gap and the optical absorption onset. However, the QSGW method is known to provide a slight overestimation of band gaps for many semiconductors.…”
Section: Comparison Of Spectroscopies With Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The foremost issue related to growth has been the high tendency to oxidization, which (when needed) has been solved with buffer and/or capping layers. 37,43,44,48 GdN single crystals have been shown to have a metallic electrical conductivity. 49 For use in a neutron detector, we are seeking a solution for a stable enough compound that is electrically conducting and contains high amounts of Gd.…”
Section: Introductionmentioning
confidence: 99%